Diet inclusion of housefly larvae and frass supplemented by Rayabold (enzyme and probiotic) on performance of laying hens and egg quality - Abolfazl Salehizadeh; Mehran Torki; Maryam Darbemamieh; Seyed Davood Sharifi (Poultry Science, 2025)
This study investigated the effects of dietary housefly larvae and frass (HFLF), with or without a multi-component supplement (Rayabold), on the performance, egg quality, and blood biochemical parameters of Lohmann LSL-Lite laying hens. A total of 192 hens, aged 56 weeks, were assigned to a 10-week feeding trial using a 4 × 2 factorial design with four HFLF inclusion levels (0 %, 5 %, 10 %, and 15 %) and two Rayabold levels (0 % and 0.05 %). A significant interaction was observed for feed intake (FI) (P = 0.0001), with hens fed 10 % and 15 % HFLF consuming less feed than those on the control or 5 % diets. Rayabold further reduced FI at higher HFLF levels. Egg production (EP) improved significantly with 10 % and 15 % HFLF (P = 0.024), while egg weight (EW) peaked at 5 % HFLF (P = 0.003) and was further enhanced by Rayabold (P = 0.008). Both HFLF and Rayabold improved feed conversion ratio (FCR), protein efficiency ratio (PER), and energy efficiency ratio (EER) (P = 0.0001), with the 15 % HFLF diet yielding the most favorable values. In terms of egg quality, higher HFLF levels (10 % and 15 %) reduced eggshell thickness (P = 0.002), while Rayabold increased it (P = 0.0007). Haugh unit values were elevated in the 10 % and 15 % HFLF groups (P = 0.043). Regarding blood parameters, 10 % HFLF lowered glucose (P = 0.0007), and both 10 % and 15 % HFLF increased cholesterol (P = 0.001), with Rayabold further elevating it (P = 0.030). Triglycerides were reduced by both 10 % HFLF and Rayabold (P = 0.050 and P = 0.0001, respectively). HFLF decreased AST (P = 0.0001) and increased albumin (P = 0.006). Complex interactions were noted for ALT and ALP (P = 0.0003 and P = 0.0001), with Rayabold mitigating the ALT increase seen at 5 % HFLF, and all treatments significantly lowering ALP compared to control. These findings support HFLF, particularly at 10–15 %, as a promising poultry feed ingredient for improving productivity and modulating physiological responses.